Unexpected chirality transition and inversion mediated by dissolution–aggregation and the odd–even effect. Issue 45 (14th November 2022) - Ma, Yafei; Cheng, Xiaoxiao; Ma, Haotian; He, Zixiang; Zhang, Zhengbiao; Zhang, Wei
Abstract : Unexpected chirality transition and inversion at molecular, macromolecular and supramolecular levels were realized by dissolution–aggregation and the odd–even effect, which is helpful for the design of advanced chirality-controllable materials. Abstract : The evolution of hierarchical chirality at macromolecular and supramolecular levels in biological systems is ubiquitous; however, achieving precise control over transitions between them in polymer systems is still challenging. Here, we reported multiple chiroptical transitions and inversion phenomena in side-chain azobenzene (Azo) polymers, PAzo-l /d - m ( m = 3, 6, 7, 8, 9, and 10, where m is the total number of atoms from the chiral stereocenter to the Azo unit), with different distances from the chiral stereocenter to the Azo unit. In the case of m = 3, an unexpected macromolecular-to-supramolecular chirality transition and inversion occurred in situ when the Azo-polymer underwent from a macromolecular-dissolved state to a supramolecular-aggregated state. To our surprise, an exciton-coupling induced multiple chiroptical inversion was observed upon the heating-assisted reassembly treatment, which was demonstrated to be driven by H - to J -aggregation transition. Furthermore, the odd–even effect was first established to regulate the supramolecular helical orientations (left- or right-handedness) in side-chain Azo-polymer assemblies.